POLITICAL ENVIRONMENT AND BUSINESS DEVELOPMENT IN THE ARCTIC Strategic opportunities and threats for Finnish companies - Tuominen, Mira (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The Arctic environment is changing constantly. There are several factors that constitute to the rate and immensity of the development. The region differs from the surrounding markets that most of the countries in the region have been used to. Therefore the purpose of the study was to understand how the political environment affects Finnish companies’ strategies and business operations. The issues analyzed were the political environment in the region, the business environment and economic development, and the opportunities and threats that the Finnish companies have in Arctic. The main theories were found from strategic management and market analysis tools. The different theories and definitions were gone through in order to understand the context of the study. This is a qualitative study that uses content analysis as its main method of analyzing the data. Therefore the data analyzed was gathered from already existing material and it was analyzed until the saturation point was found. This was done in order to minimize the risks related to using secondary data. The data collected was then categorized into themes accordingly. First the general political environment in the Arctic was studied, especially the Arctic Council and its work as the main political entity. From there the focus shifted to the business environment and the general opportunities and threats that are found from Arctic economic development. China offered another point of view to this as it represented a non-Arctic state with a keen interest on the region. Lastly the two previous objectives were combined and looked through from a Finnish perspective. Finnish companies have a great starting point to Arctic business and the operational business environment gives them the framework with which they have to operate in. As a conclusion it can be said that there are three main factors leading the Arctic economic development; the climate change, the development of technology, and the political environment. These set the framework with which the companies operating in the region must comply with. The industry that is likely to lead the development is the marine industry. Furthermore it became evident that the Finnish companies operating in the Arctic face many opportunities as well as threats which can be utilized, taken advantage of or controlled through effective strategic management. The key characteristics needed in the region are openness and understanding of the challenging environment and the ability to face and manage the arising challenges.